Impact of smallholder irrigation revitalisation programme on the exchange irrigation Scheme in Kwekwe District, Zimbabwe - Loki, Olwethu (University of Pretoria, 2023)
Dissertation (MAgric ( Extension))--University of Pretoria, 2023.